EPR and Optical Studies Of BaO-TeO2-TiO2-B2O3 Glasses Containing V4+ and Cu2+ Transitional Metal Ion. (2015) - Srinivas, B.; Hameed, Abdul; Shareefuddin, Md.; Chary, M. Narasimha
Abstract: The glasses with the composition xBaO-(30-x) TeO2-10TiO2 -58B2 O3 -V2 O5 /CuO with x=10, 15, 20, 25 mole% were prepared by melt quenching method. Cu 2+ and VO 2+ ions were used as the spin probes. X-ray diffraction studies revealed the amorphous nature of the glasses. From the EPR spectra the spin-Hamiltonian parameters were evaluated. Number of spins participating in the resonance and paramagnetic susceptibility values were evaluated. From the spin-Hamiltonian parameters of VO 2+, it was observed that the vanadyl ions exist as VO 2+ ions in octahedral coordination with tetragonal compression and have C4V symmetry with ground state dxy . The spin-Hamiltonian parameter values in the case of Cu 2+ indicated that the ground state of Cu 2+ was dx2-y2 orbital ( 2 B1g ) and the site symmetry around Cu 2+ is tetragonally distorted octahedral. From the EPR and optical data the bond parameters were evaluated.